PENERAPAN ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK DALAM PROSES PEMBERIAN IZIN MENDIRIKAN BANGUNAN ( Studi Pada Dinas Tata Ruang dan Tata Bangunan Kota Medan ) - Yuke Dwi Hidayati; Pendastaren Tarigan; Budiman Ginting; Jusmadi Sikumbang (USU LAW JOURNAL, 2015)
ABSTRACT The regulation of license found building in Medan arranged in various forms of regulation, ranging from legislation to regulation mayor, as well as a variety of related laws. But this time the legislation has not been implemented explicity. The general principle of good administration is seen as unwritten legal norms that should always be adhered by government. However, the application of the general principle of good administration currently not optimally carried out by Medan’s government, in particular spatial and office building. Presence of building that do not have license found building but sturdy buildings remain standing, which eventually became a problem for Medan’s government, because when the license found building is issued while the certificate does not exist, then the Medan’s government has done unlawful acts. In the otherwise, if Medan’s government does not give the license found building but still left the constraction is tantamount to letting a violation of law. This violates the principle of legal certainty, precision in action and also the principle of public interest. Medan’s government supervision of the implementation of the city government license found building as well as the administrative law to enforce license violation sodium absorption ratio is still unfair. The building with a very large category but have been left standing, while the buildings in the small category but not have done demolotion license. Therefore required the use of up general principle of good administration more firmly in the issuance of license found building and also required the application of strict sanctions and supervision are more optimal.